EatxCali panel: Healthy food from healthy land - International Center for Tropical Agriculture (2015)
EATxCali brings together representatives from academic and government institutions, international agencies, businesses, and civil society to rebuild food systems, and ensure that consumers have access to healthy and more sustainably produced food.